Correlation Between Fibroblast Growth Factor-23 and Pulmonary Arterial Hypertension in Hemodialysis Patients (Iranian Journal of Kidney Diseases, 2021)
Introduction. Pulmonary artery hypertension (PAH) is common in end stage renal disease (ESRD) patients undergoing hemodialysis. Fibroblast growth factor-23 (FGF-23) increases in hemodialysis but its relationship with PAH is not completely understood. The aim of this study was to evaluate the relation between FGF-23 level and development of PAH in ESRD patients undergoing hemodialysis. Methods. Patients undergoing hemodialysis for more than 6 months were enrolled in this cross-sectional study. Transthoracic echocardiography was performed to measure ejection fraction and pulmonary artery pressure (PAP) in all patients. Patients were grouped into normal PAP (PAP < 25 mmHg), elevated PAP (25 < PAP < 35 mmHg) and PAH (PAP > 35 mmHg). Parathormone hormone, calcium, phosphorus, vitamin D, and hemoglobin levels were also evaluated. Results. Eighty-five patients (48 male, 56.47%) enrolled in this study. The mean age of the patients was 51.05 ± 16.45 years. Most of the patients (49, 57.65%) had normal PAP, 20 (23.53%) had elevated PAP and 16 (18.82%) had PAH. Serum biochemical markers and demographic characteristics were not significantly related to different PAP values (P > .05). Most of the patients (42, 49.41%) had normal FGF-23 levels. There was a significant relationship between PAP groups and FGF-23 and parathormone levels, P < .001, and P < .05; respectively. FGF-23 was significantly higher in PAH and elevated PAP groups compared with normal PAP group (P < .05). Only a significant positive correlation was observed between FGF-23 levels and PAP (P < .001). Conclusion. This finding highlights the possible role of FGF-23 in the development of vascular complications in ESRD patients.DOI: 10.52547/ijkd.5940